Impact of hand-foot skin reaction on treatment outcome in patients receiving capecitabine plus erlotinib for advanced pancreatic cancer: a subgroup analysis from AIO-PK0104 - Kruger, Stephan; Boeck, Stefan; Heinemann, Volker; Laubender, Ruediger P.; Vehling-Kaiser, Ursula; Waldschmidt, Dirk; Kettner, Erika; Märten, Angela; Winkelmann, Cornelia; Klein, Stefan; Kojouharoff, Georgi; Gauler, Thomas C.; et al. (Acta oncologica, 2015)
Drug-induced skin toxicity may correlate with treatment efficacy in cancer patients receiving chemotherapy or biological agents. The correlation of the capecitabine-associated hand-foot skin reaction (HFS) on outcome parameters in pancreatic cancer (PC) has not yet been investigated.
Gesehen am 29.05.2020